English Teachers’ Perception of Security in Digital Literacy Competence - Rima Zakia; Dewi Yana (Journal on Education, 2023)
Teachers play crucial roles to promote students’ critical ability in managing information, such as integrating digital literacy skills in the learning process as a source of English learning. Therefore, teachers’ competence in digital literacy is significant. One of the competencies is a security aspect, which refers to the competence in maintaining the security of personal and other users' data. This study aims to describe the perceptions of the eighty English teachers in Batam City, Indonesia, on the security in digital literacy competence. The method of this study was descriptive qualitative research. The data collection was done by distributing online questionnaires and conducting structured interviews. It investigated the perception of the teachers toward their competence in the security aspect (personal protection, data protection, digital identity protection, and using security securely and sustainably). The result found that 86% of respondents stated that they can take security measures on digital devices and personal data during the use of digital devices in the teaching and learning process